The Influence Of Human Resource Management, Sales Management, And Strategic Management On Employee Work Productivity And Its Implications For Enhancing Enterpreneurial Spirit In Smes In The Tangerang Region - Wahyudi Wahyudi; Heri Erlangga; Yusuf Arifin; Ria Fikdawati; Denok sunarsi (Politeknik APP Jakarta, 2024)
This quantitative research investigates the influence of Human Resource Management (HRM), Sales Management, and Strategic Management on employee work productivity and its implications for enhancing the entrepreneurial spirit among Small and Medium Enterprises (SMEs) in the Tangerang region. The study employs a descriptive and associative approach, using survey methods to collect data from 150 SME employees in Tangerang. The findings reveal that effective HRM practices significantly enhance employee productivity by fostering a supportive work environment and continuous professional development. Sales Management strategies are shown to improve productivity by optimizing sales processes and customer relationship management. Strategic Management practices, including clear goal-setting and resource allocation, further boost employee productivity. Moreover, the research demonstrates that increased productivity positively impacts employees' entrepreneurial spirit, encouraging innovation and proactive business initiatives. The study concludes that integrated management practices are crucial for improving both productivity and entrepreneurial tendencies within SMEs.